Alternativní a augmentativní komunikace Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Chleboradová, Barbora (Masaryk University Press, 2019)
Title in English: Alternative and augmentative communication: Methodical texts for the MUNI 4.0 project. The study support is focused on the issue of alternative and augmentative communication. The text presents selected systems and aids applied in our and foreign practice. The text includes diagrams and tables with photographs intended for recording notes and observations obtained during the seminar, discussions and practical work with AAC devices and systems. The questions aimed at considering the possibilities of using communication systems to facilitate the communication process, the target group of users and the essential role of communication in human life are included too.